Pengaruh Orientasi Etis, Love of money dan Pengalaman Auditor pada Persepsi Etis Auditor mengenai Creative Accounting - Paramita, Pradnya; Suryanawa, I Ketut (E-Jurnal Akuntansi, 2020)
The purpose of this study was to determine the effect of Ethical Orientation, Love of money, and Auditor's Experience on the Auditor's Ethical Perceptions regarding Creative accounting. This research was conducted in all Bali Province Public Accountant Offices on auditors in each KAP. This study uses multiple linear regression analysis techniques. From the calculation results, it was found that a sample of 51 respondents who were auditors at each Bali Province Public Accountant Office and had served a minimum of 1 year of service. The analysis shows that Ethical Orientation, Love of money, and Auditor Experience significantly influence the Auditor's Ethical Perception of Creative accounting. Keywords: Ethical Orientation; Love Of Money; Auditor Experience; Ethical Perception; Auditor; Creative Accounting.